Analysis of the influence of land finance on haze pollution: An empirical study based on 269 prefecture‐level cities in China - Yang, Xiaodong; Wang, Weilong; Su, Xufeng; Ren, Siyu; Ran, Qiying; Wang, Jianlong; Cao, Jianhong (Growth and change, 2023)
Under the system of political centralization and economic decentralization, the expanding scale of land finance and the increasingly severe environmental pressure have jointly become crucial features of China's urban development. Therefore, it is of great practical significance to study the intrinsic mechanism of land finance on haze pollution for China's economy to achieve kinetic energy transformation and green development. This paper empirically analyzes the impact of land finance on haze pollution using a dynamic spatial Durbin model based on panel data of 269 prefecture‐level cities in China from 2004 to 2017. The statistical results show that haze pollution has a significant “snowball effect” and space spillover effect. Land finance has a significant positive effect on haze pollution. Land transfer both by agreement and by bid invitation, auction, and listing have significant positive effect on haze pollution. However, the promoting effect of land transfer by agreement on haze pollution is significantly higher than that of land sale by bid invitation, auction, and listing. Furthermore, regional heterogeneity implies that for cities in the eastern region, land finance is conducive to alleviating haze pollution. In contrast, for cities in the central and western regions, land finance significantly promotes haze pollution.